POLA MIKROBA PASIEN YANG DIRAWAT DI INTENSIVE CARE UNIT (ICU) SERTA KEPEKAANNYA TERHADAP ANTIBIOTIK DI RSUP SANGLAH DENPASAR BALI AGUSTUS - OKTOBER 2013 - Hamdiyati, Rachmy; Pinatih, Komang Januartha Putra; Fatmawati, Ni Nengah Dwi (E-Jurnal Medika Udayana, 2016)
MICROBES AND THEIR SUSCEPTIBILITY PATTERN TO ANTIBIOTICS IN INTENSIVE CARE UNIT (ICU) SANGLAH HOSPITAL DENPASAR BALI AT AUGUST 2013 UNTIL OCTOBER 2013 Background: Hospital is a place where people seek medical attention, but also a reservoir for some microorganism. Expecially in ICU, because ICU often soiled by microorganism and also the patient is in immunocompromised state, invasife monitoring and treatment, and contact with health workers, can induced nosocomial infection. High usage of antibiotic also induced resistance in those microorganism. Microorganism pattern and the sensisitivity is essential in each hospital to control the usage of antibiotic, and give more accurate treatment. Method: This research use cross-sectional method. The samples are clinical specimen which received by Department of Clinical Microbiology RSUP Sanglah and. Susceptibility test conducted to 50 sample which fulfill inclusion criteria. Result and conclusion: Most frequent microorganism in those sample is Pseudomonas aeruginosa (18%), Acinetobacter baumanii (18%), Staphylococcus koagulase negatif (12%), Candida spp. (10%), and Staphylococcus aureus (8%). Gram positive bacteria resist to tetracycline dan erythromycin. Gram negatif resist to cefotaxime, amikacin, cefuroxime, cephalothin and chloramphenicol. Suggestion: This kind of research can be done continuously with better sample and method.
Keywords: ICU, susceptibility pattern, microorganism pattern, antibiotic